adBoost: Thermal Aware Performance Boosting through Dark Silicon Patterning - Kanduri A.; Haghbayan M.; Rahmani A.; Shafique M.; Jantsch A.; Liljeberg P. (IEEE Computer Society, 2022)
Limitation on power budget in many-core systems leaves a fraction of on-chip resources inactive, referred to as dark silicon. An efficient run-time system that manages critical interlinked parameters of power, performance and temperature can enhance resource utilization and mitigate dark silicon. In this paper, we present a run-time resource management system for thermal aware performance boosting. The run-time system employs a dark silicon aware run-time application mapping approach that patterns active cores alongside the inactive cores in order to evenly distribute power density across the chip. This provides enough thermal headroom for boosting the frequency of active cores upon performance surges. Lower operating temperatures from patterning also allows sustaining the boosting for longer periods, improving the performance further. We design a thermal aware controller for performance boosting that decides on allocation and efficient utilization of power budget and thermal headroom resources, obtained from patterning. Our strategy yields up to 37% better throughput, 29% lower waiting time and up to 2X longer boosting periods, in comparison with other state-of-the-art run-time mapping policies.